Effect of intravenous iron on aerobic capacity and iron metabolism in elite athletes - Burden, R. J.; Pollock, N.; Whyte, G. P.; Richards, T.; Moore, B.; Busbridge, M.; Srai, S.; Otto, J.; Pedlar, C. R. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Iron-deficient athletes are often treated with long-term, low-dose iron therapy. Such treatments may be efficacious in correcting iron deficiency; however, the effect on acute and chronic iron metabolism and subsequent endurance capacity is less clear.